Uniaxial mechanical behaviors of recycled coarse aggregate concretes cast with conventional and equivalent mortar volume methods. Issue 14 (October 2022) - Yu, Yong; Yang, Bi-xuan; Liao, Zheng; Xu, Jin-jun; Hu, Shou-wang; Zheng, Yu
Among the various kinds of adjustment methods to improve the material properties of recycled aggregate concrete (RAC), equivalent mortar volume (EMV) method is widely considered as economic and effective. This is mainly because that only an extra content of natural aggregates (NAs) is needed to be added in the mixture during fabricating RAC. To objectively evaluate the method, this study conducted a series of discrete element mesoscale simulations to illustrate and compare the mechanical behaviors and failure mechanisms for conventional and EMV methods designed RAC samples under uniaxial loadings. Particularly, the influences of the replacement ratio of RAs, the mixture's water-to-cement ratio and the spatial location of coarse aggregates on the two RACs' strength and deformation characteristics were analyzed. Additionally, generic expressions used for estimating the mechanical properties of conventional and EMV methods cast RAC samples were also tried to be established in the article. It was found by this study that: (a) As the replacement ratio grows, both the conventional RAC's compressive strength and elastic modulus reduce monotonously, however, the tensile strength's variation trend is highly dependent on the relative strength of new-to-old mortar; (b) Regardless of the RAC's water-to-cement ratio, an EMV design method can always improve the elastic modulus of RAC effectively; (c) When the new mortar strength is lower than that of old mortar, adopting an EMV mix-design method notably improves the RAC's tensile and compressive strengths, however, if the old mortar strength is obviously smaller, the EMV method's enhancement to the concrete's strength is limited; (d) Variabilities for compressive and tensile strengths of EMV method designed RAC samples are commonly higher than those of conventional RAC samples; and (e) Uniaxial mechanical property of RAC sample cast either using a conventional or EMV method can both be predicted with a same formulas.